Capturing Minds: Interactive Approaches in Teaching Grammar (Ta'limning zamonaviy transformatsiyasi, 2024)
Have you ever struggled with grammar while learning English, making numerous mistakes in speaking or writing? Firstly, what is grammar itself? In language education, teaching grammar traditionally involves repetition and memorization, leaving students with a superficial understanding. However, the evolving landscape of education demands dynamic and interactive methods to captivate students' attention towards the nuances of grammar